Consolidation in multiple myeloma – current status and perspectives - Olszewska-Szopa, Magdalena; Rzepecki, Piotr (Contemporary Oncology/Współczesna Onkologia, 2014)
Although multiple myeloma (MM) is still considered an incurable disease, the treatment philosophy is changing due to the introduction of novel agents. Standard treatment consists of an induction phase and autologous stem cell transplantation in patients under 65–70 years. Prolonged treatment (consolidation and/or maintenance) is being introduced in many countries. We present a review of clinical trials dedicated to consolidation treatment in multiple myeloma. Bortezomib, lenalidomide and carfilzomib in different combinations were tested in the trials mentioned below. Although they did not prolong overall survival, the data are very promising. Three very important large clinical trials are still in progress. The results might help to establish the actual value of consolidation treatment.